Time‐dependent diffusion in undulating thin fibers: Impact on axon diameter estimation. (23rd December 2019) - Brabec, Jan; Lasič, Samo; Nilsson, Markus
Abstract : Diffusion MRI may enable non‐invasive mapping of axonal microstructure. Most approaches infer axon diameters from effects of time‐dependent diffusion on the diffusion‐weighted MR signal by modeling axons as straight cylinders. Axons do not, however, propagate in straight trajectories, and so far the impact of the axonal trajectory on diameter estimation has been insufficiently investigated. Here, we employ a toy model of axons, which we refer to as the undulating thin fiber model, to analyze the impact of undulating trajectories on the time dependence of diffusion. We study time‐dependent diffusion in the frequency domain and characterize the diffusion spectrum by its height, width, and low‐frequency behavior (power law exponent). Results show that microscopic orientation dispersion of the thin fibers is the main parameter that determines the characteristics of the diffusion spectra. At lower frequencies (longer diffusion times), straight cylinders and undulating thin fibers can have virtually identical spectra. If the straight‐cylinder assumption is used to interpret data from undulating thin axons, the diameter is overestimated by an amount proportional to the undulation amplitude and microscopic orientation dispersion of the fibers. At higher frequencies (shorter diffusion times), spectra from cylinders and undulating thin fibers differ. The low‐frequency behavior of the spectra from the undulating thin fibers may also differ from that of cylinders, because the power law exponent of undulating fibers can reach values below 2 for experimentally relevant frequency ranges. In conclusion, we argue that the non‐straight nature of axonal trajectories should not be overlooked when analyzing and interpreting diffusion MRI data. Abstract : We quantified characteristics of the time‐dependent diffusion in a toy model of undulating axons by analysis of the diffusion spectra. Microscopic orientation dispersion of the undulating thin fibers was the main factor determining the spectrum. At lower frequencies, the spectra were virtually identical to those from straight cylinders, which may lead to misinterpretation of undulations as cylinders.